2021
DOI: 10.1177/10556656211012864
|View full text |Cite
|
Sign up to set email alerts
|

Safety and Efficacy of Single-Dose Ketorolac for Postoperative Pain Management After Primary Palatoplasty: A Prospective Cohort Study With Historical Controls

Abstract: Objective: To analyze safety and efficacy of single-dose ketorolac after primary palatoplasty (PP). Design: Consecutive cohort of patients undergoing PP, comparing to historical controls. Setting: A large academic children’s hospital. Patients, Participants: A consecutive cohort of 111 patients undergoing PP (study n = 47) compared to historical controls (n = 64). Interventions: All patients received intraoperative acetaminophen, dexmedetomidine, and opioids while the study group received an additional single … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 56 publications
0
9
0
Order By: Relevance
“…Because bleeding is such a rare event in cleft palate surgery, a larger sample size would be required to prove any significant difference between the ketorolac and nonketorolac groups. The Stein et al (2021) study also found no differences in bleeding between their ketorolac and nonketorolac groups. Our results add further evidence to support the safety of ketorolac use in cleft palate surgery.…”
Section: Discussionmentioning
confidence: 80%
See 3 more Smart Citations
“…Because bleeding is such a rare event in cleft palate surgery, a larger sample size would be required to prove any significant difference between the ketorolac and nonketorolac groups. The Stein et al (2021) study also found no differences in bleeding between their ketorolac and nonketorolac groups. Our results add further evidence to support the safety of ketorolac use in cleft palate surgery.…”
Section: Discussionmentioning
confidence: 80%
“…This reached statistical significance with a P -value of <.001. A similar study investigating a single IV dose of ketorolac following their procedure (Stein et al, 2021) did not find this significant decrease in narcotic usage. This could be related to the difference in intervention protocols, as our study administered IV ketorolac intraoperatively and postoperatively and their protocol involved administration of a single dose of IV ketorolac postop.…”
Section: Discussionmentioning
confidence: 88%
See 2 more Smart Citations
“…Many of the included studies investigated the use of various analgesia techniques that aimed at reducing postoperative opioid consumption. 2,[14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29] Seven of the included studies investigated the effectiveness of bupivacaine for use in nerve block in cleft lip and/ or palate repair. 1,4,28,[30][31][32][33] All but 1 1 focused on infraorbital nerve block placement in cleft lip surgery patients.…”
Section: Pain and Analgesiamentioning
confidence: 99%